REPRODUKSI NILAI PATRIARKI DALAM WACANA FEMININITAS (Analisis Wacana Digital Konten Feminine Energy di TikTok) - Aristawati, Rozanah; Mustika Chairil, Augustin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The phenomenon of “feminine energy” content, which has gained popularity on TikTok, has drawn attention for its relation to how women understand and present femininity in digital spaces. This study aims to analyze digital discourse in TikTok videos tagged with the hashtag #feminineenergy. The study employs a qualitative approach using Rodney H. Jones digital discourse analysis method, focusing on four elements. The results show that, in terms of text, the content shapes understandings of femininity through romantic relationships, imagery, appearance, and feminine behavior. In terms of context, the discourse develops and spreads widely through creators’ productions, the use of captions and hashtags, and TikTok’s algorithm, which expands its reach. In terms of action and interaction, the discourse engages the audience through likes, comments, saves, and shares, and is reproduced via hashtags, recurring terms, and similar content formats. Regarding ideology and power, the content embodies patriarchal ideology by establishing standards for how women should behave, present themselves, and position themselves particularly within romantic relationships.